Experimental and Numerical Investigations of In Situ Alloying during Powder Bed Fusion of Metals Using a Laser Beam - Andreas Wimmer; Baturay Yalvac; Christopher Zoeller; Fabian Hofstaetter; Stefan Adami; Nikolaus A. Adams; Michael F. Zaeh (Metals, 2021)
Powder Bed Fusion of Metals using a Laser Beam (PBF-LB/M) is increasingly utilized for the fabrication of complex parts in various industrial sectors. Enabling a robust and reproducible manufacturing process is one of the main goals in view of the future success of PBF-LB/M. To meet these challenges, alloys that are specifically adapted to the process are required. This paper demonstrates the successful interplay of simulation studies with experimental data to analyze the basic phenomena of in situ alloying. The meshless Smoothed-Particle Hydrodynamics (SPH) method was employed for the numerical simulation of two-component powder systems considering both thermodynamics and fluid mechanics in the solid and the melt phase. The simulation results for the in situ alloying of stainless steel 316L blended with the aluminum alloy AlSi10Mg were enriched and validated with the data from a novel experimental test bench. The combination of both approaches can enhance the understanding of the process for in situ alloying. Therefore, future investigations of the PBF-LB/M process with multi-component powder systems can benefit from detailed numerical studies using SPH.